The OER4Schools Professional Learning Resource - University of Cambridge (2015)

The OER4Schools Professional Learning Resource - OER in Education - University of Cambridge: Faculty of Education

The OER4Schools Professional Learning Resource - OER in Education - University of Cambridge: Faculty of Education
Keywords: auto_merged

Evaluating the impact of technology-supported personalised learning interventions on the mathematics achievements of elementary students in India - Tailor, Kavita (2022)
Technology-supported personalised learning (TSPL) refers to the use of technology to personalise a learner’s experience by adjusting the pace and relevance of content based on the learner’s age, capability and prior knowledge (FitzGerald et al., 2018). Although technology has been epitomised in creating personalised and effective learning experiences for students, there are perennial debates on its role in enhancing quality, productivity and learning (Payal Arora, 2019; Zierer, 2019). This review explores the effectiveness of TSPL on the mathematics achievements of elementary students in India. This review argues that while evidence on using TSPL at scale to benefit all learners remains mixed and inconclusive, with continued iterative research, TSPL holds promise in serving learners’ needs irrespective of achievement level or socio-economic background. In doing so, this review outlines an agenda for future research to improve the efficiency, reach, and effectiveness of TSPL. This involves gaining a deeper understanding of whether TSPL works best as either a supplement or substitute in classrooms and the impacts of doing so in different quality schools. Mechanisms around how TSPL interventions can operate via low-tech mechanisms to better serve low-income communities and to advantage students of all learning abilities are also explored.
Keywords: India; education technology; elementary school; mathematics; personalised learning